Toughening of aluminum matrix nanocomposites via spatial arrays of boron carbide spherical nanoparticles. (15th January 2016) - Jiang, Lin; Yang, Hanry; Yee, Joshua K.; Mo, Xuan; Topping, Troy; Lavernia, Enrique J.; Schoenung, Julie M.
Abstract: To enhance the toughness of metal matrix nanocomposites, we demonstrate a strategy that involves the introduction of spatial arrays of nanoparticles. Specifically, we describe an approach to synthesize a microstructure characterized by arrays of fiber-like nanoparticle-rich (NPR) zones that contain spherical nanoparticles of boron carbide (sn-B4 C) embedded in an ultrafine grained (UFG) aluminum alloy matrix. A combination of cryomilling and hot-extrusion was used to obtain this particular microstructure, and the mechanical behavior and operative strengthening and deformation mechanisms were investigated in detail. When compared to an equivalent unreinforced material, the presence of the array of NPR zones contributed to a 26% increase in tensile strength. Moreover, when compared to a nanocomposite containing a homogeneous distribution of nanoparticles, a 30% increase in toughness was observed. High nanohardness values obtained for the NPR zones and the observation of "pull-out" phenomena on fracture surfaces, suggest that the NPR zones behave as "hard" fiber-like units that can effectively sustain tensile loading and thereby enhance the strengthening efficiency of sn-B4 C. Also, the presence of the array of NPR zones surrounded by nanoparticle-free (NPF) zones led to an enhancement in strength with limited loss in ductility. This behavior was rationalized on the basis of a low value of the Schmid factor in regions adjacent to NPR zones, coupled with the ease of dislocation movement in NPF zones. Finally, the ratio of the plastic zone size to the size of the "hard" NPR zones is proposed as an important factor that governs the overall toughness of the nanocomposite. Graphical abstract: Schematic of the distributions of reinforcing particles and dislocation interaction zones in composites. The shaded blue areas represent the matrix regions influenced by dislocations and the rainbow areas represent stress/strain concentrators.